Super-crosslinked microporous polymer composite membrane and preparation method thereof

Through the design of the composite film composite film of the super-cross-linking microporous polymer, combined with the surface branches and the Fu-club alkylated reaction, the traditional PA membrane and COFS membrane defects in the separation performance and chemical stability, and achieved high-performance nana Preparation of filter membranes.

CN119345914APending Publication Date: 2025-01-24SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410245628.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-05
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Traditional PA membranes and COFs membranes have defects in separation performance and chemical stability, making it difficult to achieve the requirements of high-performance nanofiltration membranes.

Method used

Adopt a combination of the polymers and surface function layers (HCPS layers) of the polymer and surface function of the super-pilot polymer of the super-connected microblog, and use the Fu-club-based reaction to achieve the interface aggregation to form an excellent separation of separation Films with performance and chemical stability.

Benefits of technology

The more complete surface shape and excellent separation performance are realized, and the problems of uneven pores of the traditional membrane and the susceptible chemical structure have good chemical and thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119345914A_ABST
    Figure CN119345914A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of membrane separation, and particularly relates to a super-crosslinked microporous polymer composite membrane and a preparation method thereof. According to the invention, the microporous membrane is selected as a basement membrane, surface functionalization is carried out on the microporous membrane to introduce aromatic ring reaction sites, and the super-crosslinked microporous polymer is prepared by an interfacial polymerization method, so that the conventional microsphere morphology is overcome, a defect-free surface structure can be realized, and the prepared composite membrane has relatively complete surface morphology and other excellent separation properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of membrane separation, and in particular relates to a super-crosslinked microporous polymer composite membrane and a preparation method thereof. Background Art

[0002] Compared with traditional separation technology, membrane separation technology has become the most promising new separation technology due to its high efficiency, energy saving, environmental friendliness and simple operation. Usually, membrane separation technology needs to use external force as a driving force to achieve accurate separation of two or more mixed substances. According to the separation principle of the membrane, separation membranes can be divided into microfiltration, ultrafiltration, nanofiltration, reverse osmosis, electrodialysis, etc. Among them, nanofiltration has characteristics between ultrafiltration and reverse osmosis, and the membrane pore size is less than 2nm. It has great applications in industrial processes such as seawater desalination, resource recovery, and sewage treatment. Nanofiltration membranes are generally composed of a porous support layer and a dense functional selection layer, in which the preparation of the selection layer determines the separation performance of the membrane. However, the polyamide (PA) functional layer that is commonly studied has a thicker selection layer and uneven pore size due to the uncontrollable monomer diffusion and reaction process, and cannot effectively balance the problem between repellency and permeability to achieve the requirements of high-performance nanofiltration membranes. In addition, the chemical structure of this membrane is also easily damaged during long-term use. Therefore, it is particularly important to design new materials with nano-porosity, structural integrity, and chemical stability.

[0003] In recent years, the use of metal organic frameworks (MOFs), covalent organic frameworks (COFs) and graphene oxide (GO) materials has become a common method for preparing high-performance separation membranes. Among them, independent COFs membranes have been successfully explored by combining the interfacial polymerization (IP) method with COFs, and then various methods have been used to apply them to porous substrates to prepare various composite membranes for separation operations. Although the COFs structure has good chemical stability and can form regular transport channels, the fabrication of COF membranes remains a major challenge due to the limitations of harsh reaction conditions and poor solution processability and film-forming properties.

[0004] Hypercrosslinked microporous polymers (HCPs) are a class of polymer materials with permanent micropores. They have been widely used in energy and environmental fields such as gas storage, carbon capture, pollutant removal, molecular separation, catalysis, drug delivery, and sensing due to their diverse synthesis methods, easy functionalization, large specific surface area, low reagent cost, and mild operating conditions. HCPs usually appear as aggregates of nanoparticles, but there is little research on hypercrosslinked microporous polymer membranes. The main reason is that the polymerization reaction is a fast kinetic process that can form a highly crosslinked network in a very short time, and the growth morphology is difficult to control. Therefore, it is still challenging to prepare defect-free hypercrosslinked microporous polymer membranes with excellent separation performance. Summary of the invention

[0005] In view of the defects of the above-mentioned traditional PA membrane and COFs membrane, the present invention provides a super-crosslinked microporous polymer composite membrane and a preparation method thereof. The prepared composite membrane has a relatively complete surface morphology and excellent separation performance.

[0006] Specifically, the present invention provides a hyper-crosslinked microporous polymer composite membrane, which includes a polymer base membrane with aromatic groups grafted on the surface and a surface functional layer (HCPs layer).

[0007] Furthermore, the polymer substrate membrane with aromatic groups grafted onto its surface is obtained by the following method:

[0008] The polymer substrate film is treated with gas plasma to perform surface functionalization, and then a surface grafting reaction is performed at a temperature of 30 to 60° C. under the action of a first reaction monomer, a catalyst, and a solvent, thereby introducing aromatic groups on the film surface.

[0009] Furthermore, the method also includes washing the polymer substrate film in an anhydrous ethanol solution for 24 hours to remove surface impurities.

[0010] Furthermore, the gas plasma is selected from at least one of Ar (containing 4% H2), O2 or N2.

[0011] Furthermore, the polymer substrate film is treated with gas plasma for 2 to 5 minutes.

[0012] Furthermore, the first reaction monomer is selected from at least one of 4-phenylbenzoyl chloride, benzoyl chloride or an aromatic derivative not containing two or more strong electron-withdrawing groups.

[0013] Furthermore, the catalyst is selected from at least one of pyridine and triethylamine.

[0014] Furthermore, the solvent is selected from at least one of toluene, anisole, dioxane or mesitylene.

[0015] Furthermore, the polymer substrate membrane can be selected from any suitable commercial microporous membrane or homemade porous membrane, for example, can be selected from at least one of polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polysulfone (PSF) or polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP).

[0016] Furthermore, the surface functional layer is prepared by a Friedel-Crafts alkylation reaction between a second reactive monomer and an aromatic group on the polymer substrate film.

[0017] Furthermore, the preparation of the surface functional layer comprises the following steps:

[0018] A polymer substrate membrane with aromatic groups grafted on its surface is placed at the interface between a first catalytic phase and a second organic phase, wherein a second reaction monomer and a crosslinking agent are added to the second organic phase to allow a Friedel-Crafts alkylation reaction to occur on the surface of the substrate membrane. The substrate membrane after the reaction is washed and dried to obtain a super-crosslinked microporous polymer composite membrane.

[0019] Furthermore, the temperature of the Friedel-Crafts alkylation reaction is 25-80°C.

[0020] Furthermore, the first catalytic phase is selected from at least one of concentrated H2SO4 and trifluoromethanesulfonic acid.

[0021] Furthermore, the second organic phase is selected from at least one of 1,2-dichloroethane and dichloromethane.

[0022] Furthermore, the second reactive monomer is at least one of benzene, biphenyl, diphenylmethane, diphenyl ether, benzo(18-crown-6) or any aromatic derivative that does not contain a strong electron-withdrawing group.

[0023] Furthermore, the cross-linking agent is selected from at least one of dimethanol formal, 1,4-dichlorobenzyl or ethylene glycol dimethyl ether.

[0024] Furthermore, the molar ratio of the second reaction monomer to the cross-linking agent is 1:3-30.

[0025] Furthermore, the washing is performed using at least one of methanol, deionized water or anhydrous ethanol.

[0026] Furthermore, the drying condition is drying at room temperature for 6 to 12 hours.

[0027] The present invention also provides a method for preparing the hyper-crosslinked microporous polymer composite membrane as described herein, which comprises the following steps:

[0028] 1) Preparation of a polymer substrate membrane with surface grafted aromatic groups: The polymer substrate membrane is treated with gas plasma to perform surface functionalization, and then a surface grafting reaction is performed at a temperature of 30 to 60° C. under the action of a first reaction monomer, a catalyst, and a solvent, thereby introducing aromatic groups on the membrane surface.

[0029] 2) Preparation of surface functional layer: placing a polymer base membrane with aromatic groups grafted on the surface at the interface between the first catalytic phase and the second organic phase, wherein a second reaction monomer and a cross-linking agent are added to the second organic phase to allow Friedel-Crafts alkylation reaction to occur on the surface of the base membrane, and washing and drying the base membrane after the reaction to obtain a super-cross-linked microporous polymer composite membrane.

[0030] Furthermore, step 1) further comprises washing the polymer substrate film in an anhydrous ethanol solution (eg, for 24 hours) to remove surface impurities.

[0031] Furthermore, in step 1), the gas plasma is selected from at least one of Ar (containing 4% H2), O2 or N2.

[0032] Furthermore, in step 1), the polymer substrate film is treated with gas plasma for 2 to 5 minutes.

[0033] Furthermore, in step 1), the first reaction monomer is selected from at least one of 4-phenylbenzoyl chloride, benzoyl chloride or an aromatic derivative not containing two or more strong electron withdrawing groups.

[0034] Furthermore, in step 1), the catalyst is selected from at least one of pyridine and triethylamine.

[0035] Furthermore, in step 1), the solvent is selected from at least one of toluene, anisole, dioxane or mesitylene.

[0036] Furthermore, the polymer substrate membrane can be selected from any suitable commercial microporous membrane or homemade porous membrane, wherein the polymer can be selected from at least one of polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polysulfone (PSF) or polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP).

[0037] Furthermore, in step 2), the temperature of the Friedel-Crafts alkylation reaction is 25-80°C.

[0038] Furthermore, in step 2), the first catalytic phase is selected from at least one of concentrated H2SO4 and trifluoromethanesulfonic acid.

[0039] Furthermore, in step 2), the second organic phase is selected from at least one of 1,2-dichloroethane or dichloromethane.

[0040] Furthermore, in step 2), the second reaction monomer is at least one of benzene, biphenyl, diphenylmethane, diphenyl ether, benzo(18-crown-6) or any aromatic derivative without a strong electron-withdrawing group.

[0041] Furthermore, in step 2), the cross-linking agent is selected from at least one of dimethanol formal, 1,4-dichlorobenzyl or ethylene glycol dimethyl ether.

[0042] Furthermore, in step 2), the molar ratio of the second reaction monomer to the cross-linking agent is 1:3-30.

[0043] Furthermore, in step 2), the washing is performed using at least one of methanol, deionized water or anhydrous ethanol.

[0044] Furthermore, in step 2), the drying condition is drying at room temperature for 6 to 12 hours.

[0045] The present invention also provides the use of the hyper-crosslinked microporous polymer composite membrane as described herein for membrane separation.

[0046] The beneficial effects of the present invention are:

[0047] The raw materials and reagents used in the present invention are low in cost and the synthesis process is simple, and it is expected to be suitable for large-scale production. The microporous membrane is selected as the substrate to provide a larger flux, which is conducive to the formation of a nanofiltration membrane with better separation performance; the chemical connection between the support layer and the functional layer is achieved by introducing the site of the subsequent polymerization reaction through the functionalization of the substrate surface, which can achieve good interface compatibility on the one hand, and overcome the defect of poor stability of the functional layer on the substrate surface on the other hand; at the same time, the preparation of super-crosslinked microporous polymers by interfacial polymerization overcomes the previous microsphere morphology and can achieve a defect-free surface structure; because the super-crosslinked structure is constructed by strong bond connection, the functional layer has excellent chemical stability and thermal stability, which is conducive to the material maintaining excellent separation performance during long-term use.

[0048] The invention has a wide range of monomer selection when preparing the super-crosslinked microporous polymer composite membrane. By selecting monomers with specific functional groups, the membrane pollution problem can be effectively solved, and the problem of reduced membrane flux caused by easy contamination and blockage during operation can be overcome. At the same time, the reaction conditions can be flexibly adjusted to effectively control the thickness of the membrane and reduce the mass transfer resistance, so that the permeability can reach 49Lm -2 h -1 bar -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 A homemade container used for interfacial polymerization in the present invention;

[0050] Figure 2 The infrared spectrum of Example 2 of the present invention;

[0051] Figure 3 The thermogravimetric curve of Example 2 of the present invention;

[0052] Figure 4 The scanning electron microscope images of the commercial microporous membrane and HCPs membrane used in the present invention;

[0053] Figure 5 is a scanning electron microscope image of a cross section of the HCPs membrane of the present invention;

[0054] Figure 6 TEM image of the cross section of Example 5 of the present invention;

[0055] Figure 7The water contact angle test results of Examples 1-6 of the present invention;

[0056] Figure 8 The surface Zeta potential test results of Examples 1-3 and 5-6 of the present invention;

[0057] Fig. 9 The filtration performance test results of Examples 1-6 of the present invention for anionic dyes with different molecular weights;

[0058] Fig.10 The filtration performance test results of Example 1-2 in the present invention after running for 24 hours;

[0059] Fig.11 The surface state of the membrane after running for 24 hours in Example 1-2 of the present invention;

[0060] Fig.12 This is a scanning electron microscope image of the BCC-PVDF membrane of the comparative example of the present invention after the reaction. DETAILED DESCRIPTION

[0061] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0062] Example 1

[0063] A preparation method of a hyper-crosslinked microporous polymer composite membrane (HBen-1) comprises the following steps:

[0064] (1) Commercial PVDF microfiltration membrane is selected as the polymer substrate, and the surface of the PVDF substrate is modified:

[0065] The PVDF microfiltration membrane was cleaned in an anhydrous ethanol solution for 24 hours, dried at room temperature, and then placed in a plasma cleaner for plasma treatment using argon (containing 4% hydrogen) and oxygen, with the discharge power adjusted to 20 W for 4 minutes to obtain a P-PVDF membrane.

[0066] (2) Grafting reaction on PVDF substrate surface:

[0067] 0.75 g of 4-phenylbenzoyl chloride, 1 mL of pyridine and 22 mL of toluene were added to a beaker in sequence to form a uniform solution under magnetic stirring. Then, P-PVDF membrane was added to the mixed solution and reacted at 40°C for 24 hours. After the reaction, unreacted monomers and other reagents on the surface were cleaned with methanol and dried at room temperature to obtain BCC-PVDF membrane.

[0068] (3) Preparation of hyper-crosslinked microporous polymer composite membrane (HBen-1):

[0069] In 5cm 2 In a glass container, the BCC-PVDF membrane was fixed between two molds, concentrated sulfuric acid was selected as the catalytic phase, and 1,2-dichloroethane was selected as the organic phase. Benzene and dimethylformal were added to the organic phase, and the content of benzene was 2 μmol / cm 2 , the content of dimethylformal is 15μmol / cm 2 The modified membrane was placed between the two phase interfaces and polymerized at 35°C for 3 days. After the polymerization, it was thoroughly washed with methanol and dried at room temperature to obtain the HBen-1 membrane.

[0070] Example 2

[0071] A preparation method of a hyper-crosslinked microporous polymer composite membrane (HBP-1) comprises the following steps:

[0072] (1) A commercial PVDF microfiltration membrane was selected as the polymer substrate, and the surface modification of the PVDF substrate was the same as step 1 of Example 1.

[0073] (2) Grafting reaction on PVDF substrate surface:

[0074] 0.75 g of 4-phenylbenzoyl chloride, 1 mL of pyridine and 22 mL of toluene were added to a beaker in sequence to form a uniform solution under magnetic stirring. Then, P-PVDF membrane was added to the mixed solution and reacted at 40°C for 24 hours. After the reaction, unreacted monomers and other reagents on the surface were cleaned with methanol and dried at room temperature to obtain BCC-PVDF membrane.

[0075] (3) Preparation of hyper-crosslinked microporous polymer composite membrane (HBP-1):

[0076] In 5cm 2 In a glass container, fix the BCC-PVDF membrane between two molds, select concentrated sulfuric acid as the catalytic phase, and 1,2-dichloroethane as the organic phase. Add biphenyl and dimethylformal to the organic phase, and the content of biphenyl is 2umol / cm 2 , the content of dimethylformal is 25μmol / cm 2 The modified membrane was placed between the two phase interfaces and polymerized at 35°C for 3 days. After the polymerization, it was fully washed with methanol and dried at room temperature to obtain the HBP-1 membrane.

[0077] Example 3

[0078] A preparation method of a hyper-crosslinked microporous polymer composite membrane (HDPO-1) comprises the following steps:

[0079] (1) A commercial PVDF microfiltration membrane was selected as the polymer substrate, and the surface modification of the PVDF substrate was the same as step 1 of Example 1.

[0080] (2) Grafting reaction on PVDF substrate surface:

[0081] 0.75 g of 4-phenylbenzoyl chloride, 1 mL of pyridine and 22 mL of toluene were added to a beaker in sequence to form a uniform solution under magnetic stirring. Then, P-PVDF membrane was added to the mixed solution and reacted at 40°C for 24 hours. After the reaction, unreacted monomers and other reagents on the surface were cleaned with methanol and dried at room temperature to obtain BCC-PVDF membrane.

[0082] (3) Preparation of hyper-crosslinked microporous polymer composite membrane (HDPO-1):

[0083] In 5cm 2 In a glass container, the BCC-PVDF membrane was fixed between two molds, concentrated sulfuric acid was selected as the catalytic phase, and 1,2-dichloroethane was selected as the organic phase. Diphenyl ether and dimethylformal were added to the organic phase, and the content of diphenyl ether was 2 μmol / cm 2 , the content of dimethylformal is 25μmol / cm 2 The modified membrane was placed between the two phase interfaces and polymerized at 35°C for 3 days. After the polymerization, it was fully washed with methanol and dried at room temperature to obtain the HDPO-1 membrane.

[0084] Example 4

[0085] A preparation method of a hyper-crosslinked microporous polymer composite membrane (HDPO-2) comprises the following steps:

[0086] (1) A commercial PVDF microfiltration membrane was selected as the polymer substrate, and the surface modification of the PVDF substrate was the same as step 1 of Example 1.

[0087] (2) Grafting reaction on PVDF substrate surface:

[0088] 0.75 g of 4-phenylbenzoyl chloride, 1 mL of pyridine and 22 mL of toluene were added to a beaker in sequence to form a uniform solution under magnetic stirring. Then, P-PVDF membrane was added to the mixed solution and reacted at 40°C for 24 hours. After the reaction, unreacted monomers and other reagents on the surface were cleaned with methanol and dried at room temperature to obtain BCC-PVDF membrane.

[0089] (3) Preparation of hyper-crosslinked microporous polymer composite membrane (HDPO-2):

[0090] In 5cm 2 In a glass container, the BCC-PVDF membrane was fixed between two molds, concentrated sulfuric acid was selected as the catalytic phase, and 1,2-dichloroethane was selected as the organic phase. Diphenyl ether and dimethylformal were added to the organic phase, and the content of diphenyl ether was 1 μmol / cm 2 , the content of dimethylformal is 5μmol / cm2 The modified membrane was placed between the two phase interfaces and polymerized at 35°C for 3 days. After the polymerization, it was fully washed with methanol and dried at room temperature to obtain the HDPO-2 membrane.

[0091] Example 5

[0092] A preparation method of a hyper-crosslinked microporous polymer composite membrane (HDPE-1) comprises the following steps:

[0093] (1) A commercial PVDF microfiltration membrane was selected as the polymer substrate, and the surface modification of the PVDF substrate was the same as step 1 of Example 1.

[0094] (2) Grafting reaction on PVDF substrate surface:

[0095] 0.75 g of 4-phenylbenzoyl chloride, 1 mL of pyridine and 22 mL of toluene were added to a beaker in sequence to form a uniform solution under magnetic stirring. Then, P-PVDF membrane was added to the mixed solution and reacted at 40°C for 24 hours. After the reaction, unreacted monomers and other reagents on the surface were cleaned with methanol and dried at room temperature to obtain BCC-PVDF membrane.

[0096] (3) Preparation of hyper-crosslinked microporous polymer composite membrane (HDPE-1):

[0097] In 5cm 2 In a glass container, the BCC-PVDF membrane was fixed between two molds, concentrated sulfuric acid was selected as the catalytic phase, and 1,2-dichloroethane was selected as the organic phase. Diphenylethane and dimethylformal were added to the organic phase, and the content of diphenylethane was 2 μmol / cm 2 , the content of dimethylformal is 15μmol / cm 2 The modified membrane was placed between the two phase interfaces and polymerized at 35°C for 3 days. After the polymerization, it was fully washed with methanol and dried at room temperature to obtain a HDPE-1 membrane.

[0098] Example 6

[0099] A preparation method of a hyper-crosslinked microporous polymer composite membrane (HDBC-1) comprises the following steps:

[0100] (1) A commercial PVDF microfiltration membrane was selected as the polymer substrate, and the surface modification of the PVDF substrate was the same as step 1 of Example 1.

[0101] (2) Grafting reaction on PVDF substrate surface:

[0102] 0.75 g of 4-phenylbenzoyl chloride, 1 mL of pyridine and 22 mL of toluene were added to a beaker in sequence to form a uniform solution under magnetic stirring. Then, P-PVDF membrane was added to the mixed solution and reacted at 40°C for 24 hours. After the reaction, unreacted monomers and other reagents on the surface were cleaned with methanol and dried at room temperature to obtain BCC-PVDF membrane.

[0103] (3) Preparation of hyper-crosslinked microporous polymer composite membrane (HDBC-1):

[0104] In 5cm 2 In a glass container, the BCC-PVDF membrane was fixed between two molds, concentrated sulfuric acid was selected as the catalytic phase, and 1,2-dichloroethane was selected as the organic phase. Dimethylformal was added to the organic phase, and the content of benzo(18-crown-6) was 2 μmol / cm 2 , the content of dimethylformal is 8μmol / cm 2 The modified membrane was placed between the two phase interfaces and polymerized at 35°C for 3 days. After the polymerization, it was thoroughly washed with methanol and dried at room temperature to obtain the HDBC-1 membrane.

[0105] The apparatus for preparing the super-crosslinked microporous polymer composite membrane by interfacial polymerization reaction of Examples 1-6 is as follows Figure 1 To prove the successful preparation of the hyper-crosslinked structure, the surface structure of Example 2 was tested using an infrared tester. Figure 2 As shown, at 1613cm -1 The characteristic absorption peak of benzene ring appeared at 727cm -1 and 694cm -1 The characteristic absorption peak of monosubstituted benzene at the position disappears, proving the successful construction of the hyper-crosslinked network. In order to further prove the existence of the hyper-crosslinked network, a thermogravimetric test was performed on Example 2. Figure 3 As shown in the figure, the temperature at which the HBP-1 membrane begins to decompose is lower than that of the PVDF-based membrane, which is due to the decomposition of the unreacted terminal methoxy groups in the hypercrosslinking reaction; but when the temperature reaches 800°C, the residual amount of the HBP-1 membrane is higher than that of the PVDF-based membrane, indicating the existence of a hypercrosslinking network. Then, the surface morphology of the membrane during the preparation process was explored, and its scanning electron microscopy was as follows Figure 4 As shown in the scanning electron microscope image, the surface of the PVDF matrix did not undergo significant changes after surface modification and grafting reaction; after interfacial polymerization, the macroporous structure on the surface disappeared, and the surface was covered by a polymer layer. In Example 1, partial accumulation of polymer occurred, which was mainly due to the fact that as the reaction time increased, part of the concentrated sulfuric acid diffused to the interface between the upper surface of the polymer layer and the organic phase to catalyze the occurrence of a hypercrosslinking reaction, making the surface rough.

[0106] In order to explore the thickness of the prepared HCPs layer, scanning electron microscopy was used to characterize the cross-section of the surface layer, e.g. Figure 5 As shown, the thickness of the HCPs layer of Examples 1-6 is about 100 nm. At the same time, the TEM image of the cross section of Example 5 was measured ( Figure 6 ), it can be seen that the thickness of the HCPs layer is about 100nm, which is similar to the test result of scanning electron microscopy. The thinner functional layer is beneficial to improving the permeability of the composite membrane.

[0107] In addition, the hydrophilicity and charge of the nanofiltration membrane surface also have an important influence on the filtration performance. The water contact angle test and surface potential test were carried out on Examples 1, 2, 3, 5 and 6, and the results are as follows: Figure 5 and 6 shown. Figure 7 a is the water contact angle value of the PVDF substrate before and after plasma treatment and after grafting. It can be seen that the surface hydrophilicity increased significantly after plasma treatment, but after the grafting reaction, the surface hydrophilicity increased to 126°. Figure 7 b is the water contact angle value of Examples 1, 2, 3, 5 and 6, all of which are less than 90°. The hydrophilicity of the surface is due to the sulfonation of some benzene ring groups in the hyper-crosslinked structure and the -O- bonds in the monomers. Figure 8 The surface potential test results of five HCPs membranes show that the surfaces of several membranes are strongly negatively charged, which is consistent with their hydrophilic surfaces. Secondly, this strong negative charge has an important influence on the subsequent retention of anionic pollutants.

[0108] The filtration performance of Examples 1 to 6 was studied respectively. Each type of membrane was cut into discs with a diameter of 2 cm and placed in a cross-flow filtration device for testing, with the working pressure set to 4 bar. Fig. 9 The filtration performance test results of Examples 1-6 for anionic dyes of different molecular weights are shown in Table 1. The dye separation results show that the degree of dye separation depends on the molecular weight of the dye. Due to the microporous structure of the HCPs layer and the strong negative charge on the membrane surface, various membranes can effectively exclude anionic dyes with a molecular weight greater than 699 g mol. -1 of dye molecules.

[0109] In order to evaluate the long-term stability of the HCPs membrane, filtration experiments were carried out on Examples 1 and 2, and the permeability and retention of the membrane for Congo red (CR) aqueous solution were measured every 2 hours. Fig.10 As shown in the figure, after 24 h, the permeability of the HBen membrane remained almost unchanged, and the rejection rate of CR remained above 95%, confirming the long-term stability of the membrane for the dye solution. Fig.11 The macroscopic images of Examples 1 and 2 after 24 hours of operation are given. It can be seen that there is no obvious adsorption of dye molecules on the circular membrane in contact with the solution, indicating that the membrane has a certain degree of anti-fouling property.

[0110] Comparative Example

[0111] At the same time, the general in-situ growth method for preparing HCPs membrane was explored. The specific implementation method is as follows: sandwich the BCC-PVDF membrane between two PTFE plate molds, prepare a polymerization solution with the same monomer concentration, add the monomer benzene, catalyst aluminum chloride, and crosslinker FDA into 3mL DCE solvent, mix evenly with ultrasound, pour on the surface of the above membrane, and react at 35℃ for 3d. After the reaction, wash it thoroughly with methanol. Use SEM to observe its surface morphology, such as Fig.12 , there was no change on the surface of the base film after the polymerization reaction, and no HCPs layer was formed on the surface, indicating that the preparation of HCPs membrane by the interfacial method is an effective implementation method.

[0112] It should be noted that the preferred embodiments of the present invention are given in the specification and drawings of the present invention. However, the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. These embodiments are not used as additional limitations on the content of the present invention. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. In addition, the above-mentioned technical features continue to be combined with each other to form various embodiments not listed above, which are all regarded as the scope of the present invention; further, for ordinary technicians in this field, they can be improved or transformed according to the above description, and all these improvements and transformations should belong to the protection scope of the claims attached to the present invention.

Claims

1. A super-crosslinked microporous polymer composite membrane, characterized in that: It comprises a polymer base film with aromatic groups grafted on the surface and a surface functional layer, The surface functional layer is prepared by a Friedel-Crafts alkylation reaction between the second reactive monomer and the aromatic group on the polymer substrate film and a crosslinking agent, The second reactive monomer is at least one of benzene, biphenyl, diphenylmethane, diphenyl ether, benzo(18-crown-6) or any aromatic derivative not containing a strong electron withdrawing group.

2. The hyper-crosslinked microporous polymer composite membrane according to claim 1, characterized in that: The polymer substrate membrane with aromatic groups grafted on the surface is obtained by the following method: The polymer substrate film is treated with gas plasma to perform surface functionalization, and then a surface grafting reaction is performed at a temperature of 30 to 60° C. under the action of a first reaction monomer, a catalyst, and a solvent, thereby introducing aromatic groups on the film surface.

3. The hyper-crosslinked microporous polymer composite membrane according to claim 2, characterized in that: The gas plasma is selected from at least one of Ar (containing 4% H2), O2 or N2, Furthermore, the first reaction monomer is selected from at least one of 4-phenylbenzoyl chloride, benzoyl chloride, or an aromatic derivative not containing two or more strong electron-withdrawing groups. Furthermore, the catalyst is selected from at least one of pyridine and triethylamine. Furthermore, the solvent is selected from at least one of toluene, anisole, dioxane or mesitylene.

4. The hyper-crosslinked microporous polymer composite membrane according to claim 1, characterized in that: The preparation of the surface functional layer comprises the following steps: A polymer substrate membrane with aromatic groups grafted on its surface is placed at the interface between a first catalytic phase and a second organic phase, wherein a second reaction monomer and a crosslinking agent are added to the second organic phase to allow a Friedel-Crafts alkylation reaction to occur on the surface of the substrate membrane. The substrate membrane after the reaction is washed and dried to obtain a super-crosslinked microporous polymer composite membrane.

5. The hyper-crosslinked microporous polymer composite membrane according to claim 4, characterized in that: The temperature of the Friedel-Crafts alkylation reaction is 25-80°C.

6. The hyper-crosslinked microporous polymer composite membrane according to claim 4, characterized in that: The first catalytic phase is selected from at least one of concentrated H2SO4 and trifluoromethanesulfonic acid, Further, the second organic phase is selected from at least one of 1,2-dichloroethane or dichloromethane, Furthermore, the cross-linking agent is selected from at least one of dimethanol formal, 1,4-dichlorobenzyl or ethylene glycol dimethyl ether.

7. The hyper-crosslinked microporous polymer composite membrane according to claim 4, characterized in that: The molar ratio of the second reaction monomer to the cross-linking agent is 1:3-30. Furthermore, the washing is performed using at least one of methanol, deionized water or anhydrous ethanol. Furthermore, the drying condition is drying at room temperature for 6 to 12 hours.

8. The hyper-crosslinked microporous polymer composite membrane according to any one of claims 1 to 7, characterized in that: The polymer substrate film is selected from at least one of polyvinylidene fluoride, polyacrylonitrile, polysulfone or polyvinylidene fluoride-hexafluoropropylene copolymer.

9. A method for preparing a super-crosslinked microporous polymer composite membrane, characterized in that: The following steps are involved: 1) Preparation of a polymer substrate membrane with surface grafted aromatic groups: The polymer substrate membrane is treated with gas plasma to perform surface functionalization, and then a surface grafting reaction is performed at a temperature of 30 to 60° C. under the action of a first reaction monomer, a catalyst, and a solvent, thereby introducing aromatic groups on the membrane surface. 2) preparing the surface functional layer: placing a polymer substrate membrane with aromatic groups grafted on the surface at the interface between the first catalytic phase and the second organic phase, wherein a second reaction monomer and a crosslinking agent are added to the second organic phase to allow Friedel-Crafts alkylation reaction to occur on the surface of the substrate membrane, and washing and drying the substrate membrane after the reaction to obtain a super-crosslinked microporous polymer composite membrane, Furthermore, step 1) further comprises washing the polymer substrate film in an anhydrous ethanol solution for 24 hours to remove surface impurities. Furthermore, in step 1), the gas plasma is selected from at least one of Ar (containing 4% H2), O2 or N2, Furthermore, in step 1), the polymer substrate film is treated with gas plasma for 2 to 5 minutes. Furthermore, in step 1), the first reaction monomer is selected from at least one of 4-phenylbenzoyl chloride, benzoyl chloride or an aromatic derivative not containing two or more strong electron-withdrawing groups, Furthermore, in step 1), the catalyst is selected from at least one of pyridine and triethylamine. Furthermore, in step 1), the solvent is selected from at least one of toluene, anisole, dioxane or mesitylene, Furthermore, the polymer substrate membrane can be selected from any suitable commercial microporous membrane or homemade porous membrane, for example, at least one selected from polyvinylidene fluoride, polyacrylonitrile, polysulfone or polyvinylidene fluoride-hexafluoropropylene copolymer. Furthermore, in step 2), the temperature of the Friedel-Crafts alkylation reaction is 25 to 80° C. Furthermore, in step 2), the first catalytic phase is selected from at least one of concentrated H2SO4 and trifluoromethanesulfonic acid, Further, in step 2), the second organic phase is selected from at least one of 1,2-dichloroethane or dichloromethane, Further, in step 2), the second reaction monomer is at least one of benzene, biphenyl, diphenylmethane, diphenyl ether, benzo(18-crown-6) or any aromatic derivative not containing a strong electron-withdrawing group, Furthermore, in step 2), the cross-linking agent is selected from at least one of dimethylformal, 1,4-dichlorobenzyl or ethylene glycol dimethyl ether, Furthermore, in step 2), the molar ratio of the second reaction monomer to the cross-linking agent is 1:3 to 30. Furthermore, in step 2), the washing is performed using at least one of methanol, deionized water or anhydrous ethanol, Furthermore, in step 2), the drying condition is drying at room temperature for 6 to 12 hours.

10. Use of the hyper-crosslinked microporous polymer composite membrane according to any one of claims 1 to 8 for membrane separation.